2016
DOI: 10.1016/j.earlhumdev.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell membrane fatty acid composition in infants fed formulas with different lipid profiles

Abstract: Background: There is growing interest in the fatty acid composition of breast milk and substitute formulas used to replace or complement infant breastfeeding. Aim: The aims of this study were to assess the impact of two follow-up infant formulas based on cow milk fat, vegetable oils and different docosahexaenoic (DHA) and arachidonic (ARA) acid content on red blood cell membrane fatty acid composition, and determine the percent saturated fatty acid (SFA) incorporation into the membrane. Study design: This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The present study also revealed that serum DHA levels were higher in breastfed infants compared to those fed CMF, even when it was supplemented with DHA. Contrary to our findings, most studies from Western countries indicated similar [22][23][24][25] or lower [36,37] blood DHA levels in 3-9-month-old, full-term, breastfed infants compared to those fed LCPUFA-supplemented formula. This discrepancy might be due to the comparable or lower DHA levels observed in breast milk versus formula in these studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study also revealed that serum DHA levels were higher in breastfed infants compared to those fed CMF, even when it was supplemented with DHA. Contrary to our findings, most studies from Western countries indicated similar [22][23][24][25] or lower [36,37] blood DHA levels in 3-9-month-old, full-term, breastfed infants compared to those fed LCPUFA-supplemented formula. This discrepancy might be due to the comparable or lower DHA levels observed in breast milk versus formula in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it remains unknown whether lactating mothers' diets affect their infants' fatty acid levels. Moreover, blood DHA levels were reported to be equivalent between breastfed infants and LCPUFA-supplemented formula-fed infants during the first several months of life in previous studies, although those studies were mostly from Western countries [22][23][24][25].…”
Section: Introductionmentioning
confidence: 97%
“…Breast milk FAs were extracted from the samples using modified Folch method (24,25). In brief, 500 µl of homogenized breast milk samples were added to a mixture of chloroform/methanol (v/v, 2:1) and 600 µl of normal saline and vortexed for 1 min.…”
Section: Milk Fatty Acid Analysismentioning
confidence: 99%
“…15,40 Se estudió su absorción e incorporación a la circulación en los niveles que alcanza la leche humana. 41,42 El recurso de LV diluida al medio con el agregado de 2 g de aceite y 5 g de azúcar por cada 100 mL debe considerarse como la última opción y hacer todos los esfuerzos para complementar las posibles deficiencias. Dos gramos de aceite de girasol, por ejemplo, aportarían aceite linoleico (54 %) y oleico (33 %), pero solo el 0,2 % de linolénico y no aporta DHA.…”
Section: áCidos Grasosunclassified